2002
DOI: 10.1016/s1044-0305(02)00378-1
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase oon-molecule reactions of transition metal complexes: The effect of different coordination spheres on complex reactivity

Abstract: Using a modified quadrupole ion trap mass spectrometer, a series of metal complex ions have been reacted with acetonitrile in the gas phase. Careful control of the coordination number and the type of coordinating functionality in diethylenetriamine-substituted ligands enable the effects of the coordination sphere on metal complex reactivity to be examined. The association reaction kinetics of acetonitrile with these pentacoordinate complexes are followed in order to obtain information about the starting comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
76
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 92 publications
(120 reference statements)
4
76
0
Order By: Relevance
“…Ion-molecule reactions in the gas-phase have been used extensively to gain information on the chemistry and reactivity of metals in coordination complexes, as well as the structures of these metal-ligand complexes [25][26][27][28][29][30][31][32][33][34]. In our studies, D 2 O and adventitious CD 3 OD were used as neutral reaction partners with several of the more abundant ions in Figure 1c to assess the degree of coordinative unsaturation of the uranyl in each of the selected species.…”
Section: Ion-molecule Reactions In the Gas-phase With D 2 O And Cd 3 mentioning
confidence: 99%
“…Ion-molecule reactions in the gas-phase have been used extensively to gain information on the chemistry and reactivity of metals in coordination complexes, as well as the structures of these metal-ligand complexes [25][26][27][28][29][30][31][32][33][34]. In our studies, D 2 O and adventitious CD 3 OD were used as neutral reaction partners with several of the more abundant ions in Figure 1c to assess the degree of coordinative unsaturation of the uranyl in each of the selected species.…”
Section: Ion-molecule Reactions In the Gas-phase With D 2 O And Cd 3 mentioning
confidence: 99%
“…This suggested that the initially formed adducts were not particularly sensitive to small changes in the He pressure. The reactions behaved as apparent bimolecular processes [41,42], and hence the rate constants are reported as such.…”
Section: Calculation Of Rate Constantsmentioning
confidence: 99%
“…To gain a better understanding of the intrinsic interactions between different uranyl species and solvent, we have begun an investigation of uranyl-anion complexes in the gas phase using ion-trap mass spectrometry (IT-MS). Several recent reports have demonstrated that intrinsic metal and metal complex chemistry can be investigated by the (controlled) addition of reagent gas to an ion trap [12][13][14][15][16][17][18][19][20][21][22], or by way of the presence of H 2 O and other small molecule contaminants within the He bath gas used to collisionally cool ions and improve trapping efficiency [23][24][25]. The reactions of uranium ions in the gas phase have been the subject of several earlier investigations.…”
mentioning
confidence: 99%